Private security guards or security and civil protection workers as future guarantors of safety in elementary schools - Perčin, Ante; Nađ, Ivan (Crisis Management Days, 2025)
After the latest incident at the Prečko elementary school, the level of security in elementary schools has once again become a priority security and social issue in the Republic of Croatia. Under pressure from parents and the general public, who, under the impression of the aforementioned incident, demanded strict supervision of elementary school buildings, the city of Zagreb, Pula and several other local communities hired security guards at the entrances to school buildings. However, immediately after the incident itself, doubts arose from the line ministry and several actors involved in the aforementioned issue, as to whether private security guards in schools are a sufficiently adequate and optimal solution. Following the above, in order to provide an argumentative explanation of the aforementioned dilemma, we will attempt to analyze possible threats and dangers in elementary schools, as well as the proposed security measures proposed by the ministry. In addition to the above, the subject of analysis will also be the protective activities of licensed security guards in accordance with their legal authorities, in proportion to future security and civil protection employees, in the capacity of new security officers in elementary schools proposed by the line ministry.